2023
DOI: 10.1088/1361-665x/aceed7
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and analysis of drop-weight damping control of MR semi-active impact resistance-based hydraulic actuator

Baizhou Ma,
Hui Huang,
Hongjian Tang
et al.

Abstract: The impact vibration caused by sudden changes in the external load of hydraulic actuators reduces the service life of hydraulic components and limits the high-precision applications of hydraulic actuators. Therefore, to improve the underdamped characteristics and impact resistance of valve-controlled cylinder systems, a semi-active impact resistance control of hydraulic actuator based on magnetorheological damper (MRD) is proposed. Firstly, based on the shear force characteristics of magnetorheological fluid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Salloom [13][14][15] et al suggested that four-way/three-position MR valves have the potential to replace various types of slide valve directional control valves in controlling hydraulic actuators. Ma [16] et al applied MR damper to the hydraulic system to improve the underdamped characteristics of the hydraulic valve-controlled cylinder system, thereby suppressing the impact vibration problem during the motion process and improving the displacement control accuracy of the hydraulic cylinder piston rod. This study can help to solve the instability of hydraulic lifting platform.…”
Section: Introductionmentioning
confidence: 99%
“…Salloom [13][14][15] et al suggested that four-way/three-position MR valves have the potential to replace various types of slide valve directional control valves in controlling hydraulic actuators. Ma [16] et al applied MR damper to the hydraulic system to improve the underdamped characteristics of the hydraulic valve-controlled cylinder system, thereby suppressing the impact vibration problem during the motion process and improving the displacement control accuracy of the hydraulic cylinder piston rod. This study can help to solve the instability of hydraulic lifting platform.…”
Section: Introductionmentioning
confidence: 99%